Eating with the Earth: Traditional Dietary Practices of the Malapandaram Tribes during Puberty, Pregnancy, and Lactation - Syamchand, Soumy; Mathew, Saji (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This study investigates the indigenous food practices of the Malapandaram tribe of southern Kerala, with a focus on traditional dietary customs during the critical reproductive phases of puberty, pregnancy, and lactation. Drawing on ethnographic and documentary sources, the research elucidates how the Malapandaram’s dietary habits are shaped by ecological resourcefulness, ritual knowledge, and gender-based taboos. The findings reveal a complex nutritional system wherein plant-based foods, wild edibles, and local preparations serve both medicinal and symbolic roles, while culturally ordained restrictions aim to safeguard maternal and child health. The study contributes to a broader understanding of how indigenous communities adapt nutritional strategies across life-cycle transitions, demonstrating the ongoing relevance of traditional knowledge in fostering nutritional well-being and cultural continuity amid changing socio-environmental landscapes.